Development of Interactive Negotiation Text Teaching Materials Using Scratch Media for 10th Grade Students at SMK PAB 2 Helvetia - Ahmad Bukhari Nasution; Muharrina Harahap (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This study aims to describe the process of developing interactive negotiation text teaching materials assisted by Scratch media for 10th grade students, describe the form of developing interactive negotiation text teaching materials assisted by Scratch media for 10th grade students at SMK PAB 2 Helvetia, and describe the feasibility of interactive negotiation text teaching materials assisted by Scratch media for 10th grade students. This study uses the Research and Development (R&D) method with the Borg and Gall model, which uses five stages in accordance with the needs, capabilities, and scope of the study. The results of this study indicate that 1) the process of developing interactive negotiation teaching materials using Scratch media for tenth-grade students began with an analysis of potential and problems through observation and interviews with teachers. The next stage was data collection, which was carried out through needs analysis, product design, and product validation by subject matter experts and media experts. The next stage was product revision to produce learning media products. 2) The suitability of teaching materials declared suitable based on the results of validation by subject matter experts covering aspects of content suitability, presentation, and language, which obtained a score of 97.91%, and the results of media expert validation covering aspects of appearance and programming, which obtained a score of 81.25%. Based on these research results, it can be concluded that the interactive negotiation text teaching material assisted by Scratch media in grade X falls into the "highly suitable" category for use in learning.